Investors' expertise, personality traits and susceptibility to behavioral biases in the decision making process - Marcin Rzeszutek; Adam Szyszka; Monika Czerwonka (Contemporary Economics, 2015)
The aim of this paper is to investigate the degree of susceptibility to behavioral biases (the certainty effect, the sunk cost fallacy, and mental accounting) among people of various levels of expertise in market investments and to determine whether this susceptibility is correlated with certain personality traits (impulsivity, venturesomeness, and empathy). The study included 200 participants: 100 retail investors who regularly invest in the Warsaw Stock Exchange and 100 students of the Warsaw School of Economics who are casually involved in investing. In this study, employing a survey methodology, we conducted a laboratory experiment that allowed us to isolate behavioral biases and personality traits and measure their influence on investors' decision-making processes. The participants filled out questionnaires containing two parts: 1) three situational exercises, which assessed susceptibility to behavioral biases, and 2) the Impulsivity, Venturesomeness, Empathy Questionnaire (IVE) Questionnaire which measures three personality traits (impulsivity, venturesomeness, and empathy). Statistical analyses demonstrated that susceptibility to behavioral biases depends on the level of expertise in market investing such that expertise increases susceptibility to behavioral biases. Some personality traits influenced the participants' likelihood of displaying these biases.
Keywords: G19; 330; investors' expertise; personality traits; behavioral biases; rationality; behavioral finance